Immunogenicity of mRNA-1273 COVID vaccine after 6 months surveillance in health care workers; a third dose is necessary. Issue 5 (November 2021) - Tré-Hardy, Marie; Cupaiolo, Roberto; Wilmet, Alain; Antoine-Moussiaux, Thomas; Della Vecchia, Andrea; Horeanga, Alexandra; Papleux, Emmanuelle; Vekemans, Marc; Beukinga, Ingrid; Blairon, Laurent
Highlights: The need for a booster dose remains an open question. Our results plead for reserving, in the upcoming months, the third dose scheme to individuals who were seronegative prior to vaccination. Six months after vaccination, a sharper decline in antibody levels is observed in naïve vaccinees compared to previously exposed participants. Summary: Objectives: Scarce data are currently available on the kinetics of antibodies after vaccination with mRNA vaccines as a whole and, with mRNA-1273, in particular. We report here an ad-interim analysis of data obtained after a 6-month follow-up in a cohort of healthcare workers (HCWs) who received the mRNA-1273 vaccine. These new data provide more insight into whether and in whom a 3rd dose could be necessary. Methods: Our study compared the anti-S antibody kinetics at 2 weeks (T1), 3 months (T3) and 6 months (T4) after the first injection, and 2 weeks after the second injection (T2). The 201 participating HCWs were stratified according to their initial serological status. The vaccine effectiveness was also assessed through a medical questionnaire. Results: We report here a marked and statistically significant antibody decrease ( P < 0.05) between T3 and T4, especially in naïve vaccinees. The analysis of potential confounding factors or known risk factors for severe COVID-19 disease did not reveal any influence on the drop observed. Six-month after vaccination, only one, symptomatic, infection was reported in our cohort. Conclusions: In a supply-limited environment, our results plead for reserving the 3rd dose scheme, in the upcoming months, to seronegative individuals prior to vaccination, especially when the serological status is easily accessible.